Merdeka Belajar Kampus Merdeka: Policy Direction and Implementation for Progress of Study Program - Adri, Helmia Tasti; Suwarjono, Suwarjono; Sapari, Yusuf; Maryani, Novi (Pusdikra Publishing, 2023)
The Merdeka Learning Campus Merdeka Program is a program that is expected to help prepare students to be better prepared to compete with the industrial world and technological advances. This program has many challenges and obstacles, both in terms of implementation and in terms of the readiness of each study program or university that will run it. This research was carried out to find out how far the implementation of Merdeka Learning Campus Merdeka was carried out by the Elementary School Teacher Education Study Program at the Faculty of Teacher Training and Education, Juanda University, Bogor. This study uses a type of qualitative research with a program evaluation methodology. The research subjects were 392 PGSD Study Program students. Based on the data obtained, it can be concluded that most of the independent campus learning programs rolled out by the government have existed in programs implemented previously at the PGSD FKIP Djuanda University Study Program. During this time the program has a different naming. Related to student concerns about the obstacles that might be faced when participating in the Merdeka Learning Campus Merdeka program is regarding the funds that will be used in implementing activities. However, on the whole the students were very enthusiastic in participating in all the existing Merdeka Learning Campus programs.